The feminist financial handbook : a modern woman's guide to a wealthy life - Conroy, Brynne (Coral Gables, FL : Mango, 2018)
Whether you want to learn more about general financial planning principles, like saving or earning a higher income, or delve into issues that disproportionately affect women, like the wage gap or the long road to economic recovery after experiencing domestic violence, "The feminist financial handbook" has stories and advice from women who have been there, worked through the struggle, and achieved personal success. Written in the same passionate tone that has made Femme Frugality a two-time nominee for Best women's finance blog, "The feminist financial handbook" acknowledges the money struggles and oppression modern women face while providing actionable steps to live your wealthiest life and achieve personal success. Author Brynne Conroy goes where other money management books fear to tread, such as motherhood and pregnancy at work, saving money when you're broke, financial betrayal, dealing with assets during and after divorce, same-sex marriage musts, and the art of negotiating in world still skewed toward favoring men.
Introduction -- Defining wealth -- Earn more -- Save more -- When one thing affects everything.
Includes bibliographical references (pages 235-241).
Keywords: Women -- Finance, Personal; BUSINESS & ECONOMICS / Budgeting